PEDAGOGICAL OPPORTUNITIES OF USING INNOVATIVE TECHNOLOGIES IN EDUCATING STUDENTS IN THE SPIRIT OF NATIONAL PATRIOTISM (Multidisciplinary Journal of Science and Technology, 2025)
This article scientifically analyzes the pedagogical opportunities of using innovative technologies in the process of educating students in the spirit of national patriotism. It examines the ways of fostering national pride, loyalty to the Motherland, respect for historical heritage, and civic responsibility among students through the effective use of digital tools, interactive methods, quest and gamification elements, mind maps, multimedia presentations, and social networks. Furthermore, the advantages of applying innovative technologies within the framework of the “Family–School–Community” cooperation are revealed, and methodological approaches aimed at strengthening patriotic education are discussed based on international experiences.